Magnetic Resonance Imaging Techniques for Post-Treatment Evaluation After External Beam Radiation Therapy of Prostate Cancer: Narrative Review - Eleni Bekou; Admir Mulita; Ioannis Seimenis; Athanasia Kotini; Nikolaos Courcoutsakis; Michael I. Koukourakis; Francesk Mulita; Efstratios Karavasilis (Clinics and Practice)
Background/Objectives: This study aimed to investigate the prognostic value of advanced techniques of magnetic resonance imaging (MRI) biochemical recurrence (BCR) after radiotherapy in patients with prostate cancer (PCa). Methods: A comprehensive literature review was conducted to evaluate the role of MRI in detecting BCR of PCa patients after external beam radiation therapy. Results: National guidelines do not recommend imaging techniques in clinical follow-up PCa. However, in 2021, the European Association of Urogenital Radiology (ESUR), the European Association of Urological Imaging (ESUI), and the PI-RADS Steering Committee introduced the Prostate Imaging for Recurrence Reporting (PI-RR) system. PI-RR incorporates the MRI biomarkers in the post-treatment process. In the last decade, a growing number of clinical researchers have investigated the role of various MRI techniques in BCR. Conclusions: The integration of advanced MRI technologies into clinical routine marks the beginning of a new era of BCR with accuracy.